GLUEBALL MASSES AND THE STRING TENSION IN SU(2) LATTICE GAUGE-THEORY WITH TWISTED BOUNDARY-CONDITIONS - Stephenson, P; Teper, M (1989)
We carry out a preliminary calculation of the glueball mass spectrum and the effective string tension in SU(2) lattice gauge theory with 't Hooft's twisted boundary conditions. We make semi-quantitative comparisons with recent analytic results in small volumes and with previous Monte Carlo calculations for periodic boundary conditions. We find a reasonable measure of agreement between the form of our results and those of the analytic calculations. © 1989.